Удосконалення моделі ризику виробничого травматизму на підприємстві - Євтушенко, Ольга Володимирівна (My University, 2014)
В роботі проаналізовано зв’язок ризику травмування із заходами попередження нещасних випадків на підприємстві. Представлена схема дії на ризик травмування профілактичних заходів і засобів з охорони праці. Запропоновано загальні рекомендації щодо вибору профілактичних заходів, які можуть бути використані при вдосконаленні проектів управлінських рішень щодо забезпечення безпечних умов праці працівників підприємств різних галузей промисловості України. In order to optimize of prevention activities in the field of occupational safety is necessary to have quantitative characteristics and risk assessment by type, sources of hazards and causes of industrial accidents and measures to minimize or neutralize them. As the state of injury or risk of accidents at work is a random with a high degree of uncertainty, then for the purposes of Health and Safety management most commonly used approach based on logical analysis. In research analyzes the relationship of risk of injury with the prevention measures at the enterprises. The presented scheme of the risk of injury prevention activities and facilities for safety. Set quantitative characteristics for use in the practice of planning and forecasting — an extremely difficult task. From a formal point of view, this is because of the three main reasons: lack of reliable statistical data, the inability of conduction the experiments, the unpredictability of human behavior. It was suggested general advices on choosing preventive measures that can be used to improve project management decisions to ensure safe working conditions of employees enterprises Ukraine.
Keywords: кафедра екології та екоменеджменту; безпека; праця; виробничий травматизм; ризик; нещасний випадок; риск; security; work; injuries; risk; accident